Federalism and constitutional change - Livingston, William S. (London, 1956)
This study is conceived as an attempt to view the federal system in a somewhat different light from that in which it is ordinarily displayed. That federalism is a legal concept and poses vast problems of a legal nature is not to be denied; but it has appeared to me that a better understanding of the nature of federal government can be secured by trying to picture its workings as a process in which the diversified elements that compose a federal state integrate and compromise their differences, rather than as a set of institutions and procedures whose operation is wholly determined by the legal norms and structures.
Keywords: Political Science